Sonographic Reference Ranges for the Thyroid Gland in Euthyroid Term Newborns - Mikołajczak, Aleksandra; Borszewska-Kornacka, Maria Katarzyna; Bokiniec, Renata (American Journal of Perinatology, 2015)
Objective This study aims to establish the reference ranges for normal thyroid gland (length, width, depth, and volume) in healthy term Polish neonates within the first week of life to aid in the comparative evaluation of infants with suspected thyroid disease.Study Design A total of 148 term neonates from mothers with normal thyroid function were examined during their first week of life. Ultrasound examination was performed in both longitudinal and transverse projections to create reference value percentile charts for thyroid volume in healthy term neonates.Results Median (range) width, depth, and length were 0.714 (range, 0.470–0.959), 0.677 (range, 0.527–0.960), 2.07 (range, 1.540–2.870) cm for the right lobe of the thyroid: and 0.720 (range, 0.535–1.010), 0.678 (range, 0.521–0.952), 2.015 (range, 1.620–2.730) cm for the left. Volumes for right lobe, left lobe, and both lobes combined were 0.502 (range, 0.228–0.931), 0.511 (range, 0.294–0.959), and 1.014 (range, 0.526–1.849) mL.Conclusion Diagnostic ultrasound examination of the thyroid in the neonate is a simple and useful method for assessment of thyroid gland disease and neonatal health. This study provides robust normative data for Polish newborns. Furthermore, we have found different values compared with other countries, particularly Scotland, which underlines the importance of establishing population-based data.
Keywords: newborn; thyroid sonography; thyroid volume; references thyroid values